Determining climate change impacts on viticulture in Western Australia - Barnuud, Nyamdorj Namjildorj (Curtin University, 2012)
Global climate model simulations indicate 1.3°C to 1.8°C increase in the Earth’s average temperature by middle of this century above the 1980 to 1999 average. The magnitude and rate of change of this projected warming is greater than the average warming during the last century. Global climate models project an even higher degree of warming later in the century also due to increasing grrenhouse gases concentrations in the atmosphere from human activity. Impacts of future climate change on viticulture are likely to be significant as viticulture requires a narrow climate range to produce grapes of suitable quality for premium wine production.In this thesis, impacts of climate change on winegrape growing conditions across the Western Australian wine regions were spatially and temporally examined by utilising fine resolution downscaled climate projections. Relationships between climate variation and grape maturity or key quality attributes of Cabernet Sauvignon, Shiraz and Chardonnay were modelled from measured fruit and climate data along a natural climate gradient encompassing a 5°C range in winegrape growing season average temperature. Potential future climate change impacts on grape quality were quantitatively evaluated by driving the grape quality models with the downscaled climate projections.Analyses of climate conditions for winegrape growth were carried out under future climate projections for the Western Australian wine regions. A total of 10 global climate models forced with an A2 emission scenario were downscaled. Of these models, the MEDRES Miroc3.2 and CSIRO Mk3.5 climate models, which indicated the low and high warming ranges (projections of these models will be referred as low and high range warming, hereafter) across the study regions, were selected to take into account the uncertainty of future climate change for impact assessment. Our results indicate increasingly warmer and drier climate conditions for the Western Australian wine regions. The current October to April average temperature (averaged across the regions) is projected to be 0.5°C to 1.5°C warmer by 2030, respectively. The magnitude of the warming will likely be uneven across the regions. For example, 0.1 to 0.3°C higher average temperature during October to April period has been projected for the northern regions than the southern regions by 2030, depending on the warming ranges. On the other hand, rainfall is projected to decrease across the regions under the future scenario we assessed in this study. By 2030, annual rainfall, averaged across the regions, is projected to decline by 5 to 8%, respectively, under the low and high warming ranges of climate change under the A2 emission scenario. Among seasons, the greatest decline in rainfall is projected to occur during spring. On average, up to 8% and 19% decline in spring rainfall is projected respectively under the low and high warming ranges by 2030.The magnitude of these changes are projected to increase as time progresses. For example, by 2070, averaged across the study regions, our modelling results show current mean temperature during October to April is projected to be between 1.1°C and 3.9°C warmer, but the annual rainfall is likely to be 15 to 24% lower than the current climate averages (1975 to 2005) under the A2 scenario.Maturity dates of the studied varieties are projected to advance asymmetrically across the study regions. For example, Cabernet Sauvignon may reach 22 °Brix total soluble solid maturity about 4 and 7 days earlier respectively for the northern and the southern regions by 2030 under the low warming range. Our results also indicate maturity date shifting a further 8 and 18 days earlier by 2070 for the northern and the southern regions respectively under the same warming range. Patterns of this maturity date shifting is likely to be similar under the high warming range. However, the magnitude of advancement is projected to be doubled.If no adaptive measures are implemented future climate change will likely reduce wine quality due to declining concentrations of berry anthocyanins and acidity under a warmer climate. The reductions of berry quality attributes are likely to be more pronounced in the warmer northern wine regions compared to the cooler southern regions. For example, Cabernet Sauvignon current median anthocyanins concentration is projected to decline by about 12% and 33% for the warmer northern regions, and about 6 to 18% for the cooler southern wine regions respectively by 2030 and 2070 under the high warming range. In contrast, the maximum decline in Cabernet Sauvignon anthocyanin concentration under the lower warming range is projected to be small, up to 5% for the cooler southern and up to 8% for the warmer northern regions by 2070. Shiraz anthocyanins concentration decrease pattern is similar to that of Cabernet Sauvignon, however, our modelling indicates the magnitude is smaller, with maximum of 18% for Swan District and about 11% for the southern regions by 2070 under the high warming range.Modelled impacts of climate change on grape titratable acidity are also region and variety specific. Among the varieties studied, Chardonnay exhibits the highest decline in median titratable acidity across the regions (17% for the Margaret River and 42% for the Swan District regions), followed by Shiraz (7% for the Margaret River and 15% for the Peel regions) and Cabernet Sauvignon (no change for Blackwood and 12% for the Swan District regions) by 2070 under high climate warming. On the other hand, the median titratable acidity levels are less impacted by low warming scenario (maximum decline is 4% for Shiraz only by 2070).Under the future warming scenarios studied in this thesis currently established wine regions and wine styles across the Western Australian wine regions are likely to be affected to the extent that some regions may not be conducive to premium wine production, while for some regions changing the variety may be the only option to adapt to the climate change. For example, by 2070, under high warming range Swan District, Perth Hills, and some parts of the Peel and Geographe regions are projected to be suited more to producing fortified wines or table grapes due to high average growing season temperature (>24°C). In this future climate the present cool climate southern regions are likely to have the same climate conditions that currently prevail in the warmer Swan District. Apparent differences in currently planted varieties between the cooler southern and warmer northern regions clearly indicate the need to adapt to the warming climate in the southern wine regions.Analysis of other potential factors that influence viticulture such as frequency of hot days, vapour pressure deficit and disease pressure were examined. The results indicated that winegrape fungal disease pressure will likely decrease across the regions due to the declining rainfall, potentially lessening the need for spraying during the growing season. On the other hand, there will likely be increased frequency of hot days and elevated vapour pressure deficit. The impacts of these, combined with the decreasing rainfall during growing season will potentially drive irrigation demand higher requiring altered water management under climate change.Climatically, most of the Western Australian wine regions are known as premium wine producing areas. The results from this study indicate potential challenges of climate change for the Western Australian wine industry. Under the future climate scenarios examined, some currently warmer regions may become less suitable for premium quality wines due to the increased temperature, which is projected to be out of the optimum temperature range for premium wine production. For most of the other regions, the challenge will likely be a decreased grape quality required to produce premium wine with the current varieties. Suitable adaptation strategies may be required to maintain the current market reputation. Furthermore, the warmer and drier conditions under climate change is likely to necessitate revised water management across the wine growing regions, especially some regions which are already limited by available water for grape production. However, the magnitude of the impacts is projected to be dependent upon the magnitude of future climate change.